Penggunaan Media Video Pembelajaran Terhadap Peningkatan Aktivitas Belajar Siswa di Man 02 Kepahiang - Bahrin, Bahrin; Ayuni, Rossa; Utami, Cindi Tri (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to determine the effect of using educational video media on improving students’ learning activity in Economics subject at MAN 02 Kepahiang. The background of this research is the low level of student learning activity, characterized by a lack of active participation such as reluctance to ask questions, take notes, and engage in discussions during conventional learning processes.This research uses a quantitative approach with a quasi-experimental method. The subjects of the study consisted of two classes: class XI-5 as the experimental class using educational video media, and class XI-2 as the control class using conventional learning methods. The instruments used included observation of learning activities and tests (pretest and posttest).The results showed a significant improvement in learning activity in the experimental class. The average pretest score of the experimental class students was 69.2, which increased to 76.3 in the posttest, with the percentage of learning mastery increasing from 24% to 76%. Meanwhile, in the control class, the improvement was not significant, with the average score increasing from 69.7 to 72.8 and the mastery level only reaching 38.1%.